Serum globulin changes in patients with craniocerebral trauma. - Auer, L (1976)
Investigations of serum total protein, albumin, alpha-1, alpha-2, alpha-2M, beta- and gamma-globulin changes are reported in 48 patients with craniocerebral trauma. Only alpha-2 and alpha-2M globulins showed important variations, the first rising to three to four times normal values (112% on average) and directly correlating with the amount of tissue lesions. Alpha-2M changes were rather irregular with a tendency to severe decrease during the first days in patients with a bad prognosis. Reasons for non-regular changes of alpha-2M are discussed. Alpha-1 globulin showed a similar though less marked increase. Gamma globulin, on average, was diminished in the first week.